Fetomaternal outcomes of abruptio placentae: a tertiary care experience - Farheen, Khateeb; Muddeeregowda, Raksha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Abruptio placentae is the premature separation of a normally situated placenta after 20 weeks of gestation and before delivery of the fetus. It is a major cause of antepartum hemorrhage and is associated with significant maternal and perinatal morbidity and mortality. This study aimed to determine the incidence, risk factors, complications and fetomaternal outcomes of abruptio placentae in a tertiary care center. Methods: This retrospective study was conducted at Bangalore Medical College and Research Institute, Bengaluru, including Vani Vilas Hospital and GOSHA Hospital, from January 2021 to August 2021. Demographic details, obstetric history and maternal risk factors were recorded. Gestational age was determined by last menstrual period and ultrasonography. Diagnosis was based on clinical features and ultrasonographic findings and confirmed by retroplacental clots or hematoma at delivery. Other causes of antepartum hemorrhage were excluded. Results: The incidence of abruptio placentae was 0.95%. The most affected age group was 20–25 years and 52% were multiparous. Hypertensive disorders of pregnancy were present in 38.46% of cases, with severe preeclampsia in 23.07%. Vaginal delivery occurred in 66.35% cases, while 33.65% underwent cesarean section. Anemia was observed in 52.88% cases. Stillbirth occurred in 56.73% cases. Major maternal complications included postpartum hemorrhage (23.07%), disseminated intravascular coagulation (12.5%) and ICU admission (21.15%). Conclusions: Abruptio placentae remains a significant contributor to maternal and perinatal morbidity and mortality. Early identification of high-risk pregnancies, timely referral, availability of blood bank facilities and prompt multidisciplinary management are essential to improve outcomes.